ANALISIS FAKTOR DETERMINAN PENAMPILAN BERBUSANA MAHASISWI ASRAMA DI YOGYAKARTA - Yuliana Eka Putri (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2016)
The purpose of this study is to describe thedeterminants of the appearance of dressingin the West Kalimantan Dormitory (DaraDjuanti). This research is a kind ofquantitative descriptive research, usingquestionnaire and documentation. Dataanalysis technique using descriptive analysiswith saturated sample technique. Validity testand instrument reliability using productmoment and Reliability test using AlphaCronbach formula. The results showed thatthe determinants of dress appearanceaccording to most respondents in thecategory high enough with a relativefrequency of 50%. The determinant factor ofdress appearance consists of internal factorsand external factors with the explanation asfollows. (1) Internal factors of dressappearance consisting of personality, bodyshape, age, and knowledge of most studentsof West Kalimantan Dormitory (DaraDjuanti) included in category enough withfrequency 47,5%. (2) External factors ofdress appearance consisting of communityenvironment, association and informationmedia most of the female students in enoughcategory with frequency 87,5%